Corneal Keloid Mimicking a Recurrent Limbal Dermoid - Gaviria, Juan G.; Johnson, Daniel A.; Scribbick, Frank (Journal of pediatric ophthalmology and strabismus, 2005)
We report a 12-year-old boy who presented with the clinical appearance of a limbal dermoid recurrence. Histologic study of the lesion revealed it to be a corneal keloid. In the event of a recurrent mass following dermoid excision, keloid should be considered in the differential diagnosis. J Pediatr Ophthalmol Strabismus 2005;42:189–190.